INTRADERMAL NEVUS WITH GRANULOMATOUS REACTION: A CASE REPORT (International Journal of Food and Nutritional Sciences, 2022)
Nevus is a localized benign abnormality of melanocytic system Melanocytic nevi are usually acquired lesion. They are most common in head, neck and trunk. I here report an unusual case of intradermal nevus with granulomatous inflammation and giant cell reaction. A 30 years old female patient presented with brief history of mole over right cheek from 2 years. Swelling was firm, nonmobile and tender. Histological finding shows melanocytic proliferation in the dermis. Superficially melanocytes are in nest and deeper dermis shows presence of granuloma with giant cell reaction. Inflammatory infiltrate is composed of lymphocytes and plasma cells. Histopathology was suggestive of intradermal nevus with granulomatous reaction.